Optimalisasi Pelayanan Mitigasi Bencana Banjir di Karangbinangun Lamongan Agar Masyarakat Peduli Akan Pentingnya Lingkungan - Zahrotul Arofah; Anggraeny Puspaningtyas (Public Administration Dept, Faculty of Social and Political Science, 2023)
Mitigation is an effort with a goal tominimize impact of disasters by carrying out proper planning. Geological and hydrometeorological disasters are disasters that are often experienced by Indonesia. In Indonesia hydrometeorological disasters such as floods are affected by strong westerly winds and world climate change. Inappropriate land use change also supports the occurrence of this disaster. The purpose of this study was to determine the standard of flood mitigation services in Karangbinangun Lamongan and to recommend forms of flood disaster mitigation in Karangbinangun Lamongan. This study uses analysis with qualitative research methods. The analysis was carried out with reference to Law No. 24 of 2007 concerning Disaster Management. The results of this study are that there are 14 Public Service Standards for flood disaster mitigation.